1990
DOI: 10.1016/0014-5793(90)81108-z
|View full text |Cite
|
Sign up to set email alerts
|

Neutron scattering study of the (γ‐B) catalytic domains of complement proteases Cl̄r and Cl̄s

Abstract: The catalytic domains of Cir and Cis, comprising the C-terminal region of the A chain (y), disulphide-linked to the B chain, were obtained by limited proteolysis of the native proteases with chymotrypsin and plasmin, respectively, and studied by small angle neutron scattering. For Cfs (y-B), a molar mass of 45 000 + 5000 g/mol, and a relatively large radius of gyration (Z&) of 28 f 1 A were determined, excluding a single globular domain. The corresponding values for Cir (y-B), (90,000 g/mol, R8 = 34 f 1 A) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…Also, our model is consistent with neutron diffraction studies (Zaccaı ¨et al, 1990), which concluded to a "loose packing of the γ-B subunits". The neutron scattering amplitude radius of gyration calculated from the atomic coordinates of our model (not taking into account the carbohydrates) is 38.5 Å, whereas a value of 34 ( 1 Å was determined experimentally (Zaccaı ¨et al, 1990). These two values may be considered reasonably consistent in view of the multidomain structure and flexibility of the assembly and considering the uncertainties inherent to the model.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Also, our model is consistent with neutron diffraction studies (Zaccaı ¨et al, 1990), which concluded to a "loose packing of the γ-B subunits". The neutron scattering amplitude radius of gyration calculated from the atomic coordinates of our model (not taking into account the carbohydrates) is 38.5 Å, whereas a value of 34 ( 1 Å was determined experimentally (Zaccaı ¨et al, 1990). These two values may be considered reasonably consistent in view of the multidomain structure and flexibility of the assembly and considering the uncertainties inherent to the model.…”
Section: Discussionsupporting
confidence: 91%
“…According to our model, the distance between the centers of gravity of the monomers is 62 Å, which compares well with the value of about 70 Å estimated from electron microscopy pictures (Weiss et al, 1986). Also, our model is consistent with neutron diffraction studies (Zaccaı ¨et al, 1990), which concluded to a "loose packing of the γ-B subunits". The neutron scattering amplitude radius of gyration calculated from the atomic coordinates of our model (not taking into account the carbohydrates) is 38.5 Å, whereas a value of 34 ( 1 Å was determined experimentally (Zaccaı ¨et al, 1990).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Complement proteins C2, C4, and C1 inhibitor were isolated from human plasma by means of published procedures (18 -20). For the determination of protein concentrations the following absorption coefficients (A (1%, 1 cm) at 280 nm) and molecular weights were used: C1r, 12.4 and 86,300 (21); C1s, 14.5 and 79,800 (21, 11); C1 s ␥-B, 18.3 and 47,520 (22,11); C2, 10.0 and 100,000 (18); C4, 8.2 and 205,000 (23,24); C1 inhibitor, 3.86 and 105,000 (25). The absorption coefficients (A (1%, 1 cm) at 280 nm) used for the recombinant fragments ap-SP (17.0) and CCP 2 -ap-SP (16.4) were calculated from their amino acid composition by the method of Edelhoch (26), and their molecular weights were determined by mass spectrometry analysis (see "Results").…”
Section: Methodsmentioning
confidence: 99%
“…The line (R3 = constant X Mr) in logarithmic coordinates is for globular proteins (0) such as ribonuclease (Rg = 13; Mr = 13,900), lysozyme (Rg= 14; Mr= 14,300), papain (Rg= 16; Mr = 23,000) and hemoglobin (Rg =23.5; Mr =64,500). For further details see reference (23).…”
Section: Q2 ( 1 03 X A-2)mentioning
confidence: 99%